1997
DOI: 10.1097/00005176-199707000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of 6-Mercaptopurine in Crohn's Disease Patients During the Perioperative Period: A Preliminary Evaluation of Recurrence of Disease

Abstract: Although the underlying pathophysiologic reasons leading to the high relapse rate after intestinal surgery in Crohn's disease are unknown, we conclude that treatment with 6-mercaptopurine in the perioperative period may be warranted to help prevent the recurrence of Crohn's disease after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Another pediatric study showed a clinical response in about 70% of children with CD; more than half were able to discontinue prednisone completely during the first 6 months of 6-MP use (175). Recurrence of disease after surgery may be prevented with 6-MP, as was shown in a small, uncontrolled study by Kader et al (176).…”
Section: Experience In Childrenmentioning
confidence: 86%
“…Another pediatric study showed a clinical response in about 70% of children with CD; more than half were able to discontinue prednisone completely during the first 6 months of 6-MP use (175). Recurrence of disease after surgery may be prevented with 6-MP, as was shown in a small, uncontrolled study by Kader et al (176).…”
Section: Experience In Childrenmentioning
confidence: 86%
“…Azathioprine and MP in combination with other immunosuppressants like cyclosporine, tacrolimus, methotrexate, thalidomide or infliximab have proven efficacy in CD perianal fistulas with prolonged fistula closure in 30–40% of cases 16–19 . Moreover, both thiopurines help to prevent the recurrence of CD after surgery, especially in high risk patients, with a NNT of four in 2 years to prevent one clinical relapse 20–23 …”
Section: Efficacymentioning
confidence: 99%
“…They are frequently prescribed for patients in whom first‐line therapy fails, in particular those who are steroid‐dependent or who do not have a response to systematic corticosteroids 5, 6 . Both AZA and 6‐MP have proven their efficacy for the induction of remission in active Crohn’s disease, 7, 8 for maintaining remission and sparing steroids in quiescent steroid‐dependent Crohn’s disease, 9, 10 or for preventing recurrence after surgery in Crohn’s disease 11–15 . For use in ulcerative colitis, efficacy has been proven for maintenance therapy, but only as alternative treatment 16 …”
Section: Introductionmentioning
confidence: 99%